The orchard - Heller, Peter, 1959- (Vintage Contemporaries/Vintage, an imprint of Penguin Random House LLC, 2025)
"Hayley and her seven-year-old daughter Frith live in a rustic cabin with no electricity in the foothills of Vermont's Green Mountains. A renowned translator of Tang dynasty poetry, Hayley walked awayfrom her career and her addict husband to raise Frith alone in a land populated not by ambition-fueled academics but by hawks, beavers,and other wild things--including their exuberant Bernese Mountain dog Bear. They get by on what little they earn from their overgrown apple orchard and the syrup they make from their maple trees. Frith-- precocious, homeschooled, and a voracious reader--considers herself queen of this backwoods paradise. She is too young to understand the pain and regret that have followed her mother here"--